Analysis of the psychometric properties of the Indonesian version of the McMaster family assessment device general functioning subscale (FAD GF-12) - Setiana, Elgi Selis; Tondok, Marselius Sampe (Jurnal Ilmiah Psikologi Terapan, 2024)
This research aimed to evaluate the reliability and validity of the McMaster Family Assessment Device subscale General Functioning (GF-12), an assessment tool with 12 indicators of family educational function in high school present in the Indonesian form. A purposive non-random sampling method was employed on 103 adolescent students, aged 16-18 years, consisting of 75 females and 27 males currently in high school. The results showed that the questionnaire was valid and reliable. The GF-12 subscale items showed r value of 0.5-0.8 compared to the table index of 0.3 using the pearson correlation. The Cronbach's alpha value for the GF-12 subscale items was 0.8. In light of these results, the GF-12 questionnaire of the Indonesian version is a valid instrument for assessing family function. This showed that the level of family functioning in adolescents can be assessed more accurately. The results are recommended as the basis for a more accurate assessment of the Indonesian cultural and linguistic context. Furthermore, it is suggested a standard for researchers, practitioners, and educators who focus on adolescent welfare issues.